2016
DOI: 10.1002/adsc.201600270
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic [3+2] Cycloadditions of Barbiturate‐Based Olefins with 3‐Isothiocyanato Oxindoles: Highly Diastereoselective and Enantioselective Synthesis of Dispirobarbiturates

Abstract: Catalyzed by a Cinchona‐based thiourea, the [3+2] cycloadditions of barbiturate‐based olefins with 3‐isothiocyanatooxindoles proceeded readily, and furnished dispirobarbiturates in excellent chemical yields with excellent diastereo‐ and enantioselectivities. The absolute configuration of dispirobarbiturates was firmly confirmed by an X‐ray single crystal structure analysis. A reaction mechanism was proposed to account for the enantioselective formation of dispirobarbiturates.magnified image

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…A similar domino Michael/cyclization reaction between 409 and cyclic methyleneindolinones 592 in the presence of the cyclohexanediamine‐derived thiourea catalyst 581 , as reported by Jing, Qin, and co‐workers, provided the trispirooxindole derivatives 591 in good to high stereoselectivities (Scheme ) . Zhao and co‐workers also employed the barbiturate‐based alkenes 594 in the reaction with 409 catalyzed by a quinine‐derived thiourea catalyst 438 to obtain dispirobarbiturate derivatives 593 in excellent yields and stereoselectivities (Scheme ) . While the authors proposed a concerted [3+2] cycloaddition mechanism for this reaction, we do not see how they excluded the stepwise domino Michael/cyclization reaction mechanism proposed by other groups for similar reactions.…”
Section: Multifunctional Catalystsmentioning
confidence: 69%
See 1 more Smart Citation
“…A similar domino Michael/cyclization reaction between 409 and cyclic methyleneindolinones 592 in the presence of the cyclohexanediamine‐derived thiourea catalyst 581 , as reported by Jing, Qin, and co‐workers, provided the trispirooxindole derivatives 591 in good to high stereoselectivities (Scheme ) . Zhao and co‐workers also employed the barbiturate‐based alkenes 594 in the reaction with 409 catalyzed by a quinine‐derived thiourea catalyst 438 to obtain dispirobarbiturate derivatives 593 in excellent yields and stereoselectivities (Scheme ) . While the authors proposed a concerted [3+2] cycloaddition mechanism for this reaction, we do not see how they excluded the stepwise domino Michael/cyclization reaction mechanism proposed by other groups for similar reactions.…”
Section: Multifunctional Catalystsmentioning
confidence: 69%
“…Zhao and co‐workers also employed the barbiturate‐based alkenes 594 in the reaction with 409 catalyzed by a quinine‐derived thiourea catalyst 438 to obtain dispirobarbiturate derivatives 593 in excellent yields and stereoselectivities (Scheme ) . While the authors proposed a concerted [3+2] cycloaddition mechanism for this reaction, we do not see how they excluded the stepwise domino Michael/cyclization reaction mechanism proposed by other groups for similar reactions. On the other hand, Xie and co‐workers employed racemic 3‐nitro‐2 H ‐chromenes 596 and 409 as the substrates in the asymmetric domino Michael/cyclization reaction for the synthesis of spirooxindole derivatives.…”
Section: Multifunctional Catalystsmentioning
confidence: 83%
“…Also in 2016, Zhao and coworkers described the asymmetric synthesis of dispirobarbiturates by the formal [3 + 2] cycloaddition reaction of 3-isothiocyanato oxindoles and alkylidene barbiturates as dipolarophiles, catalyzed by thiourea 5 derived from quinine and 4-methylbenzoic acid (Scheme 23). [41] The acid additive seems to promote tautomerization of the isothiocyanato oxindole into its enol form, adding a hydrogen donor domain to the system that may be better suited to interact with the bifunctional thiourea catalyst than the carbonyl form. The reaction was complete in less than one minute and showed overall good to excellent yields, excellent diastereoselectivity and good to excellent enantioselectivity.…”
Section: -Isothiocyanato Oxindoles As Formal Dipolesmentioning
confidence: 99%
“…Introduction of trifluoromethyl group into dispirobarbituric acid derivatives is of great interest for us. Despite the numerous bioactive spirobarbituric acid derivatives that have been reported, we found that it was in 2016, Zhao and coworkers first used barbiturate‐based olefins and 3‐isothiocyanato oxindoles to prepare chiral dispirobarbituric acid derivatives (Scheme ) . We realized that within this reaction system, barbiturate‐based olefins performed as strong electron‐deficient alkenes.…”
Section: Introductionmentioning
confidence: 98%